Comparative Genomics of Lactiplantibacillus plantarum: Insights Into Probiotic Markers in Strains Isolated From the Human Gastrointestinal Tract and Fermented Foods - Garcia-Gonzalez, Natalia; Bottacini, Francesca; van Sinderen, Douwe; Gahan, Cormac G. M.; Corsetti, Aldo (Frontiers in Microbiology, 2022)
Lactiplantibacillus (Lpb.) plantarum is a versatile species commonly found in a wide variety of ecological niches including dairy products and vegetables, while it may also occur as a natural inhabitant of the human gastrointestinal tract. Although Lpb. plantarum strains have been suggested to exert beneficial properties on their host, the precise mechanisms underlying these microbe-host interactions are still obscure. In this context, genome-scale in silico analysis of putative probiotic bacteria represents a bottom-up approach to identify probiotic biomarkers, to predict desirable functional properties and to identify potentially detrimental antibiotic resistance genes. In this study we characterized the bacterial genomes of three Lpb. plantarum strains isolated from three distinct environments (strain IMC513 (from the human GIT), C904 (from table olives) and LT52 (from raw milk cheese)). Whole-genome sequencing was performed combining Illumina short reads with Oxford Nanopore long reads. Phylogenomic analyses suggested highest relatedness between IMC513 and C904 strains which were both clade 4 strains, with LT52 positioned within clade 5 within the Lpb. plantarum species. Comparative genome analysis performed across a number of Lpb. plantarum representatives highlighted the genes involved in key metabolic pathways as well as those encoding potential probiotic features in these new isolates. In particular our strains varied significantly in genes encoding exopolysaccharide biosynthesis and in contrast to strains IMC513 and C904, the LT52 strain does not encode a Mannose-binding adhesion protein. The LT52 strain is also deficient in genes encoding complete pentose phosphate and the Embden-Meyerhof pathways. Finally, analyses using the CARD and ResFinder databases revealed that none of the strains encode known antibiotic resistance loci. Ultimately the results provide better insights into the probiotic potential and safety of these three strains and indicate avenues for further mechanistic studies using these isolates.